Big tech and platform-enabled multinational corporate capital(ism): the socialisation of capital, and the private appropriation of social value. (14th September 2022) - Pitelis, Christos
Abstract: I explore the relationship between theory and prediction in political economy and organisational economics, employing the works of Keith Cowling and Stephen Hymer as case examples of prediction-aiding good theory. I develop the insights of the two scholars by leveraging key ideas from classical economics and applying the result to the platform-enabled, market-assisted organisational economy. Based on that I suggest that the emergence and rise of platform-enabled Big Tech, unicorns and the 'sharing economy' are both aligned with and partly predictable. I go on to hazard some further predictions about the future of the corporation and capitalism and discuss research opportunities.